The impact of political instability on international tourism in the Garden Route - Hunter, Matthew-John McKenzie (The IIE, 2019)
Tourism is one of the key drivers of South Africa’s (SA’s) economy. SA has endured a political transformation from an apartheid government to a democratic one, opening it’s tourism to the rest of the world. Political certainty is salient in attracting international tourists. SA has experienced an increase in political instability, the concern for the safety of tourists, and public turmoil. Which is showcased through a 4.6% lower average increase in tourism in comparison to global averages in 2017. This study attempts to understand the implications political instability, tourism safety, and public turmoil have on SA’s tourism industry. A quantitative research design was applied, through sampling 24 international tourists in the Garden Route. Primary research has been implemented through a cross-sectional survey design. A questionnaire was distributed electronically and physically, making use of closed-ended questions. Data was analysed and interpreted through descriptive statistics. The main finding of the study was that political instability, the lack of safety for tourists, and public turmoil have a negative effect on SA’s tourism sector as they deter international tourists from travelling to the country. Furthermore, this study contributes by confirming the findings mentioned by Ferreira & Perks (2016), in their publications called “Theoretical Overview of the Political Climate Variables Influencing Tourism in South Africa”.
Keywords: political instability; public turmoil; safety of tourists; tourism; international tourists